APLICAÇÃO DE VITAMINAS COMO TECNOLOGIA DE AMENIZAÇÃO DE ESTRESSE EM MILHO - SILVA FILHO, Marcelo Xavier; COSTA, Antonio Cesar; VENDRUSCOLO, Eduardo Pradi; ARAÚJO, Thales Oliveira; SERON, Cássio de Castro; MARTINS, Murilo Battistuzzi (ANAIS DO ENIC, 2023)
-